The incidence of preeclampsia based on maternal characteristics: a cohort study - Johariyah Johariyah; Detty Siti Nurdiati; Widyawati Widyawati (Poltekkes Kemenkes Yogyakarta, 2021)
Preeclampsia is one of the leading causes of maternal mortality. Research on the characteristics of mothers who are at risk for preeclampsia at the first pregnancy visit is important to prevent the incidence of preeclampsia. This study aims to determine the incidence of preeclampsia based on maternal characteristics. A cohort study design was used to determine the effect of maternal characteristics on the incidence of preeclampsia Sample was pregnant women who made their first pregnancy visit. The analysis was chi-square. The results showed that the factors that were significantly associated with the occurrence of preeclampsia were: primigravida (P-value: 0.00), family history of preeclampsia (P-value: 0.00), occupation (P-value:0.04), and insurance ownership (P-value:0.03). A risk assessment of preeclampsia in pregnant women can be carried out at the time of the first antenatal visit.